Description of Knowledge, Attitude, and Delays in Seeking Treatment of Leprosy in Tuban, 2018 - Zulfah Fitria Fajriahadun Ni'mah; Praba Ginandjar; Nissa Kusariana; Retno Hestiningsih (Jurnal Kesehatan Masyarakat (Undip), 2020)
The high proportion of Multibaciller cases and the finding of defects in leprosy cases in Tuban caused the low awareness of sufferers in seeking treatment as early as possible after finding out. The purpose of this study is to describe the knowledge, attitudes, and delays in seeking treatment for lepers in Tuban on 2018. This research is a descriptive study with cross sectional study design. The population of this study is leprosy patients registered in the leprosy cohort data of the Health Office on Tuban Regency who are still doing leprosy treatment until 2018. The sampling technique uses proportional random sampling, so there were 112 lepers to be sampled. The variables that be studied were the level of knowledge, attitudes, and delay in seeking treatment. These variables can be measured using a questionnaire and observasion of leprosy cards. Based on research results that more than half of lepers have good knowledge (60.7%), and good attitude (67.9%), but there are still many patients who delayed in seeking treatment is 63.4%. It can be concluded that most of the lepers have good knowledge and attitude, but there are still many lepers have delays in seeking treatment.